Studi Pemanfaatan Catu Daya Hibrida PLTS 3,7 kWp Dan PLN Pada Instalasi Pengolahan Air Limbah Desa Pemecutan Kaja Denpasar Bali - Arimbawa, Aries; Kumara, Satya; Hartati, Rukmi Sari (Majalah Ilmiah Teknologi Elektro; Vol 15 No 2 (2016): (July - December) Majalah Ilmiah Teknologi Elektro, 2016)
Abstract —Pemecutan Kaja waste treatment plant (WTP) was a community treatment plant located in one of Denpasar city ward to process sewerage produced by community members. The WTP uses radial flow anaerobic system which mainly consists of rabic pro and up flow tanks. The water produced by the WTP was released to nearby river as it already met envinronmental quality standard. The WTP was driven by an electric pump to circulate sewer material within the process flow. The pump was fed by hybrid power supply combining 3.7 kW solar PV and power from utility grid. The WTP was operated by village council of Pemecutan Kaja. The study presented here was result of firstly, evaluation on the utilization and performance of solar PV plant, and secondly, to propose managerial model that can manage the plant effectively and sustainably. The study found that daily average energy produced bythe PVplant was 23.59 kWh yielding cost of energy at IDR 7,766/kWh. Experiment to clean filters of the plant reduced daily energy consumption from 8.84 kWh to 3.05 kWh or 65%. Household that connected to the plant pay monthly subscription currently at IDR 10,000.  However, for sustainable operation of the plant, the household need to pay IDR 51,654. Keywords: Renewable Energy, Solar PV, Hybrid Power Supply, Waste Treatment, Managerial Model Abstrak — Instalasi Pengolahan Air Limbah (IPAL) Desa Pemecutan Kaja adalah IPAL yang terletak di salah satu lingkungan kota Denpasar yang berfungi untuk mengolah air limbah yang dihasilkan oleh anggota masyarakat. IPAL ini meggunakan sistem radial flow anaerobic yang terdiri tangki rabic pro dan tangki up flow filter. Air hasil pengolahan limbah dapat langsung disalurkan ke sungai karena sudah memenuhi baku mutu limbah cair. IPAL ini menggunakan pompa listrik untuk mengalirkan limbah menuju tangki penyaringan. Pompa ini mengunakan catu daya hibrida PLTS 3,7 kW dan PLN. IPAL ini dikelola langsung oleh masyarakat desa Pemecutan Kaja. Hasil penelitian yang ingin dicapai adalah pertama, evaluasi pemanfaatan dan kinerja PLTS, kedua  merencanakan model pengelolaan agar IPAL dapat berfungsi secara optimal dan berkelanjutan . Hasil penelitian ini menemukan bahwa rata-rata energi listrik yang dihasilkan PLTS yaitu 23,59 kWh/hari dengan harga energi sebesar Rp.7.766,25/kWh. Percobaan untuk membersihkan filter pada IPAL dapat mengurangi konsumsi energi harian dari 8,84 kWh menjadi 3,05 kWh atau 65%. Rumah tangga yang menjadi pengguna IPAL saat ini membayar iuran sebesar Rp 10.000. Namun, untuk operasi yang berkelanjutan dari IPAL, rumah tangga perlu membayar sebesar Rp 51.654. Kata kunci: Energi Terbarukan, PLTS, Pembangkit Listrik Hybrid, Pengolahan Limbah, Model Pengelolaan
Keywords: Energi Terbarukan; PLTS; Pembangkit Listrik Hybrid; Pengolahan Limbah; Model Pengelolaan